Promotion Trends and Impact of New Media Advancement for Business Marketing - Costica ROMAN; Ruxandra BEJINARU (Communications of International Proceedings, 2021)
The aim of this paper is to analyze a series of novelty aspects with a major relevance in the field of marketing but with a special emphasis on this activity in the digital environment. This exploratory research, of qualitative type, has as specific objectives the presentation and interpretation of the importance that the following key notions have both in theory and in practice, namely: new media trends in online marketing; adapting the marketing activity to the new technologies; and online promotion. Addressing these issues aims to identify solutions to facilitate the transition of business from classic marketing to online marketing by highlighting the advantages of the latter but also by exemplifying the actions needed to be taken for this purpose. In the first section we will describe the expression "new media" which is very current and is used to identify all new media, such as blogs, social networks, podcasts, sites for uploading and sharing video content and any device connected to the internet, used to access these communication channels. In the second section we will discuss the new online marketing process compared to the traditional one by emphasizing the advantages, opportunities and differences between them. The third section is devoted to a series of examples on the variants of online promotion strategies that have been successfully developed and applied recently by global companies. In the conclusion section we will summarize the connections between the analyzed concepts and we will insist on the major impact they have in the real economy in which digitalization is advancing at a fast pace.
Keywords: New Media; Online Promotion; Digital Marketing; Online Marketing Mix.